First Chemical Investigation of Korean Wild Mushroom, Amanita hemibapha subsp. javanica and the Identification of Anti-Helicobacter pylori Compounds - Seulah Lee; Akida Alishir; Tae Wan Kim; Dong-Min Kang; Rhim Ryoo; Changhyun Pang; Mi-Jeong Ahn; Ki Hyun Kim (Pharmaceuticals, 2022)
Amanita hemibapha subsp. javanica (Amanitaceae) is an edible Korean wild mushroom. A. hemibapha subsp. javanica is often confused with A. subjunquillea, known as the East Asian death cap, which is potentially fatal when ingested. This study aimed to conduct the first chemical investigation of A. hemibapha subsp. javanica, which resulted in the isolation of seven fatty acid derivatives (1–7) and three steroids (8–10) from the MeOH extract of its fruiting bodies, and their structures were determined by comparing their NMR spectroscopic data with those previously reported, along with the data from LC/MS. Compound 1 was reported previously without the identification of its absolute configuration; its structure, including the absolute configuration was confirmed for the first time, in this study, by using 1H NMR and its fragmentation patterns in MS/MS data, and LC/MS analysis. A recently developed method using competing enantioselective acylation (CEA) coupled with LC/MS analysis was applied for determining the absolute configuration of compound 1, which revealed the 11S-configuration. In the anti-Helicobacter pylori activity test, compound 3 showed antibacterial activity against H. pylori strain 51 with 38.0% inhibition, comparable to that of quercetin (34.4% inhibition) as a positive control. Specifically, compound 4 displayed the most potent antibacterial activity against H. pylori strain 51 with 80.5% inhibition at the final concentration of 100 μm with a MIC50 value of 72 μm. These findings suggested that the active compound 4 is a natural antibiotic that may be used in the development of novel antibiotics against H. pylori. In addition, the first chemical investigation of A. hemibapha subsp. javanica revealed that this mushroom can serve as a promising natural source for the bioactive natural products.